Total Phosphorus Input to the Cache la Poudre River in Northern Colorado. (1st February 2015) - Son, Ji‐Hee; Goodwin, Stephen; Carlson, Kenneth
ABSTRACT: : The objectives of this study were to monitor total phosphorus concentrations and loads along the Cache la Poudre River in Northern Colorado as it flows from a pristine area through urban regions and, finally, through mixed land uses. The study attempted to evaluate the sources and influences of total phosphorus under different hydrologic conditions. Nine sampling events were completed from April 2010 to May 2011 to assess the influence of various hydrologic conditions on aqueous and riverbed sediment total phosphorus concentrations. Total phosphorus concentrations and loads exceeded the in‐stream limits proposed by the Colorado Department of Public Health and Environment in all observed hydrologic conditions, and nonpoint sources were significant in high‐flow conditions. Reducing nutrients only at water resource recovery facilities (WRRFs) could not achieve the in‐stream limits without substantial reduction of non‐point‐source loads. The study exposed a need for flexibility in WRRF discharge limits based on the overall total phosphorus load in the river from other sources.